Pengaruh Nilai – Nilai Sosial terhadap Toleransi Sosial Kaum Ibu dalam Tradisi Merempah Sebagai Kearifan Lokal Masyarakat Desa Gunung Sakti Kecamatan Manna Kabupaten Bengkulu Selatan - Erawati, Agustya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the influence of social values ​​on the social tolerance of mothers in the merempah tradition as the local wisdom of the Gunung Sakti village community, Manna District, South Bengkulu Regency. The type of research conducted is quantitative research using a survey method approach. The population in this study were 50 mothers involved in the merempah tradition. The sample was determined using a purposive sampling technique. Data collection techniques were observation, questionnaires, interviews, documentation. Hypothesis testing in this study used a partial sample t-test of independent variables. The results of the study showed that the variable (X) social values ​​had a significant influence on the variable (Y) social tolerance. This is supported by the results of the coefficient of determination analysis with a result of 0.801, this is evidenced by the results of the t-test calculation of 13,915 while in the t-table 2.010 at a significance level of 5% which means that Ha is accepted, namely there is an influence of social values ​​on the social tolerance of mothers in the berempah tradition as the local wisdom of the Gunung Sakti village community, Manna District, South Bengkulu Regency and rejects Ho with a coefficient of determination of 0.801. Keywords: Social Values, Social Tolerance, Mothers, Spice Tradition